Urban exile theories, methods, research practices - Dogramaci, Burcu 1971-; Aygün, Ekaterina; Hetschold, Mareike; Karp Lugo, Laura; Lee, Rachel (intellect, 2023)
Explores cities of exile from different perspectives and presents different methods and sources for exile and urban studies. The essays are written by internationally recognized scholars, and contain a wide range of themes including mapping, oral history, queerness, photography. This book will make a significant contribution to the theory and methodology of research on historical exile, cities and modernities, as well as present multidisciplinary exile research from an urban perspective. With a blend of case studies, and theoretical approaches, it interweaves histories of modernism and exile in different urban environments and focuses on historical dislocations in the first half of the twentieth century, when artistic and urban movements constituted themselves in global exchange. Although this book takes a historical perspective, it is written with an awareness of current flight movements and will make a significant contribution to the theory and methodology of research on exile. The knowledge of previous historical exile experiences is important for the understanding of contemporary flight movements: after all, these are not singular phenomena. For migration movements in the first half of the 20th century and for those of today, it is equally possible to speak of urban centres of attraction for refugees: Today, Berlin is a European metropolis of exile; in the 1930s and 1940s, Paris, Prague, London, New York, Istanbul and Shanghai were destinations for refugees.
Keywords: Geschichte 1900-2000; Cities and towns / History / 20th century; Exiles / History; Cities and towns; Exiles; Methode; Theorie; Exil; Stadt; Aufsatzsammlung